Monogenic Autoinflammatory Diseases with Mendelian Inheritance: Genes, Mutations, and Genotype/Phenotype Correlations - Martorana, Davide; Bonatti, Francesco; Mozzoni, Paola; Vaglio, Augusto; Percesepe, Antonio (Frontiers in Immunology, 2017)
Autoinflammatory diseases (AID) are a genetically heterogeneous group of diseases caused by mutations of genes encoding proteins which play a pivotal role in the regulation of the inflammatory response. In the pathogenesis of AID, the role of the genetic background is triggered by environmental factors through the modulation of the innate immune system. Monogenic AID are characterized by Mendelian inheritance and are caused by highly penetrant genetic variants in single genes. During the last years, remarkable progress has been made in the identification of disease-associated genes by using new technologies, such as next generation sequencing (NGS), which has allowed the genetic characterization in undiagnosed patients and in sporadic cases by means of targeted resequencing of a gene panel and whole exome sequencing. In this review, we delineate the genetics of the monogenic AIDs, report the role of the most common gene mutations and describe the evidences of the most sound genotype/phenotype correlations in AID.